Development of a mercury sensor using voltammetry techniques based on waste tire carbon electrodes modified with zinc oxide doped ion imprinted polypyrrole - Dayanti, Meri; Alva, Sagir; Lelifajri, Lelifajri; Nazaruddin, Nazaruddin; Julinawati, Julinawati; Sukoma, Sukoma; Fonna, Syafrizal; Ahmad Kamal Arifin,; Siti Aishah Hasbullah,; Kacaribu, Andriy Anta; Said, Muhammad; Suhud, Khairi (Penerbit Universiti Kebangsaan Malaysia, 2025)
Waste Tire Carbon (WTC) was chosen as the carbon source for fabricating the mercury sensor. Tires are inherently carbon-rich (88%) and are considered elastomer blends. While WTC has been used as a sensor for mercury detection, the resulting sensitivity has been relatively low. Therefore, modifications to the working electrode are necessary to improve mercury detection. One such modification involves using nanoparticles, specifically zinc oxide (ZnO) doped with ion-imprinted polypyrrole (PPy). The modified WTC electrodes with ZnO and PPy were characterized using Fourier Transform Infrared (FT-IR) and Scanning Electron Microscopy (SEM). A 0.1 M KCl solution was used as the supporting electrolyte. The calibration curve was linear, with an R² of 0.9977, a concentration range of 0.01-8.00 ppm, a limit of detection (LoD) of 0.03 ppm, and a limit of quantification (LoQ) of 0.07 ppm, with %RSD below 2%. Selectivity tests were conducted to measure Hg2+ ions by adding the metal ions, namely Ag+ and Pb2+. The test results showed that the electrode had good selectivity, although there was a decrease in the peak current from 16 mA to 15,45 mA. These results indicate that the developed method is highly sensitive and selective to Hg concentrations.